2017
DOI: 10.1177/0363546516682235
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship After Meniscal Allograft Transplantation According to Articular Cartilage Status

Abstract: Our findings showed that MAT was an effective symptomatic treatment in knees with advanced bipolar chondral lesions. However, better graft survival can be expected when articular cartilage is intact or if chondral damage is limited to a unipolar lesion. MAT should be considered before the progression of chondral damage to a bipolar lesion for better graft survivorship and should be performed cautiously in arthritic knees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 23 publications
6
102
1
Order By: Relevance
“…33,48,49,56 Noyes et al 30 found that patients who required a concurrent osteochondral autograft transfer had a significant decline in estimated survival, despite reporting satisfying PROMs; other authors reported similar findings, with a higher failure rate in cases of greater chondral damage. 26,35,36,46 In our analysis, we decided to use the number of patients with an OCS > 3 as a predictor in the regression model as this allowed for aggregation of a higher number of data; we could not find any predictive association with regard to both PROMs and failure rates, and this is in agreement with the hypothesis that patients with advanced chondral damage should not be denied MAT. The qualitative analysis, however, highlighted that controversies remain in the literature regarding the role of chondral damage in determining transplant failure, with the need for higher quality studies with more homogeneous definitions of subgroups and comparable statistical analysis techniques.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…33,48,49,56 Noyes et al 30 found that patients who required a concurrent osteochondral autograft transfer had a significant decline in estimated survival, despite reporting satisfying PROMs; other authors reported similar findings, with a higher failure rate in cases of greater chondral damage. 26,35,36,46 In our analysis, we decided to use the number of patients with an OCS > 3 as a predictor in the regression model as this allowed for aggregation of a higher number of data; we could not find any predictive association with regard to both PROMs and failure rates, and this is in agreement with the hypothesis that patients with advanced chondral damage should not be denied MAT. The qualitative analysis, however, highlighted that controversies remain in the literature regarding the role of chondral damage in determining transplant failure, with the need for higher quality studies with more homogeneous definitions of subgroups and comparable statistical analysis techniques.…”
Section: Discussionsupporting
confidence: 52%
“…44,53,73,74 However, with the advent of modern chondral restoration procedures, an increasing number of surgeons have extended the indications to patients with advanced chondral defects, such as those with an OCS IV or IRCS > 3, and several recent studies demonstrated that these patients can expect comparable functional results. 33,36,38,40,43,46,52,55 Interestingly, some authors have observed that patients with greater chondral damage did not report worse clinical outcome compared with those with lower chondral damage even though their grafts seemed to fail earlier. Kempshall et al 40 divided patients into two subgroups, those with IRCS 3b and those with IRCS > 3b; the groups had comparable PROMs but a difference of 1.1 years in survivorship in favor of the group with lesser chondral damage was noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilot randomisedcontrolled trial in 2018 confirmed MAT had better outcomes at 1 year compared to physiotherapy (12). Authors have reported positive patient outcome measures following MAT using the KOOS, IKDC, Lysholm, Tegner, and SF-12 scores (13)(14)(15)(16). It remains unclear what proportion of any improvement might be due to MAT alone or from potential concomitant procedures (17), and it is also unclear whether MAT has any long-term chondroprotective effect (18).…”
Section: Introductionmentioning
confidence: 99%